The Role Of Servant And Hypno Leadership In Creating Student Service Innovation - Arya Gemilang Bimasakti; Endang Suswati; Tri Cicik Wijayanti (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study is situated within the growing emphasis on service innovation in faith-based higher education, where leadership practices shape students’ moral orientation and service engagement. Within Buddhist higher education contexts, leadership formation involves not only organizational management but also the internalization of spiritual and ethical values. This study provides an interpretive exploration of how Servant Leadership and Hypno Leadership are enacted and experienced in fostering service-oriented leadership practices among students. A qualitative descriptive design was employed, drawing on observations, in-depth interviews, and documentation involving lecturers, Buddhist religious counselors, temple leaders, and active students. Data were analyzed using the interactive model of Miles and Huberman through processes of condensation, categorization, and thematic interpretation. The findings illuminate that leadership formation occurs through interconnected processes of academic learning, experiential training, role modeling, and socio-religious engagement. These processes are understood as cultivating empathy, responsibility, collaborative orientation, persuasive communication, emotional regulation, and adaptive service practices grounded in Buddhist ethical principles. Rather than establishing causal relationships, this study offers contextually embedded insights into how spiritual–moral leadership values and psychologically informed communication practices interact in supporting service-oriented innovation within a faith-based higher education setting.